1995
DOI: 10.1002/lsm.1900160408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nd:YAG laser on wound healing processes: Clinical and immunohistochemical findings in rat skin

Abstract: This study showed a slower wound healing in the high-energy lased tissues. A similar healing in the low-energy lased tissues and in the incisions with the conventional scalpel was observed. The differences in the distribution of matrix proteins during healing and the coagulation of the tissues, which were exposed to low-energy laser treatment, might be the explanation for the minimal scarring, contraction, and pigmentation of the lased tissues as compared to conventional incisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Thus, laser is promising coadjutant treatment that can be used in the photodynamic therapy [12,13], stimulate cell differentiation, reduction of inflammation, and tissue repair [14][15][16][17]. Previous studies demonstrated that the specific parameters of low-level laser therapy LLLT can stimulate the deposition of collagen by fibroblasts [18] and proliferation of osteoblasts [19], as well as increase the mitochondrial activity and synthesis of ATP [20]. Once applied to cultured odontoblast-like cells, the LLLT increased cell metabolism as well as the synthesis of proteins and alkaline phosphate activity [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, laser is promising coadjutant treatment that can be used in the photodynamic therapy [12,13], stimulate cell differentiation, reduction of inflammation, and tissue repair [14][15][16][17]. Previous studies demonstrated that the specific parameters of low-level laser therapy LLLT can stimulate the deposition of collagen by fibroblasts [18] and proliferation of osteoblasts [19], as well as increase the mitochondrial activity and synthesis of ATP [20]. Once applied to cultured odontoblast-like cells, the LLLT increased cell metabolism as well as the synthesis of proteins and alkaline phosphate activity [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the photo-stimulation mediated by the LLLT, in addition to increase ATP synthesis [6], produces an analgesic effect [7][8][9] and stimulates cell division [10], accelerating tissue healing [11][12][13]. Some specific laser types also have the capacity to stimulate the synthesis and deposition of collagen matrix by fibroblasts [14][15][16], and the increase of mitochondrial activity and cell metabolism [8] and proliferation [12].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Some specific types of laser can also stimulate fibroblasts to synthesize and deposit collagen matrix. [8][9][10] A number of in vitro investigations using a wide range of cell cultures have provided different data concerning cell proliferation 11,12 and differentiation, 13 DNA and bone protein synthesis, 1,[14][15][16] and bone tissue formation without genotoxic or cytotoxic damage. 17 Unfortunately, these studies have particular irradiation setups and different methodologies, so that the results obtained cannot be compared with or extrapolated to others.…”
mentioning
confidence: 99%